1
$\begingroup$

1) If an ≥ 0 and bn ≥ 0, prove that lim sup anbn ≤ (lim sup an)(lim sup bn)

2) If {an} and{bn} are non-negative sequences and {bn} converges, prove that lim sup anbn = (lim sup an)(lim bn).

I am not sure how to show these two similar proofs. Please show details so I can understand the process.

Thank you.

$\endgroup$
  • $\begingroup$ Do you have a good understanding of what the $\limsup$ is? Please, write down your definition of $\limsup$ in the question, since there are different definitions of it. $\endgroup$ – Crostul Feb 17 '15 at 19:52
1
$\begingroup$

Let be $n\geq0$. For all $k\geq n$ , one has$$a_{k}\leq\sup_{k\geq n}a_{k}$$ and also$$b_{k}\leq\sup_{k\geq n}b_{k}.$$ Since everything is non-negative, one gets$$a_{k}b_{k}\leq\left(\sup_{k\geq n}a_{k}\right)\left(\sup_{k\geq n}b_{k}\right)$$ whence$$\sup_{k\geq n}a_{k}b_{k}\leq\left(\sup_{k\geq n}a_{k}\right)\left(\sup_{k\geq n}b_{k}\right).$$ To conclude, one takes the limit $n\rightarrow+\infty$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.